Therapeutic management and outcome of patients with advanced systemic mastocytosis treated with midostaurin: A comprehensive real‐life study in the French national healthcare database. Issue 5 (29th August 2022) - Rossignol, Julien; Nizard, Sandra; Blanc, Anne‐Sandrine; Filipovics, Anne; Lortet‐Tieulent, Joannie; Bouktit, Hassiba; Poinsot, Gwendoline; Schmidt, Aurélie; Raguideau, Fanny; Hermine, Olivier
Abstract: Advanced Systemic Mastocytosis (Adv‐SM) is rare and has a poor prognosis. Midostaurin (Rydapt ® ) is one of the few treatments for Adv‐SM in Europe. The study aims were to describe the characteristics of patients treated with midostaurin, their treatment modalities, outcomes, and serious events requiring hospitalization. This retrospective observational study was conducted using the French National Healthcare Database (SNDS) and included adult Adv‐SM patients treated with midostaurin between 01‐01‐2012 and 09‐30‐2018. Kaplan‐Meier method was used to assess survival and treatment duration. Eighty‐one patients were included: 37 with Aggressive Systemic Mastocytosis (SM) (46%), 31 with SM with an Associated Hematological Neoplasm (38%), and 4 with Mast Cell Leukemia (5%). The SM subtype was undetermined in 9 patients (11%). The median age was 67 years; 64% of patients were male. Over the mean follow‐up of 11.4 months, median midostaurin treatment duration was 8.4 months and 28 patients (35%) were still under treatment at the end of the study. One‐year and 5‐year overall survival rates estimated since the time of diagnosis were 83% and 56%, respectively. Twelve serious events (among those frequently reported during clinical trials and compassionate use) requiring hospitalization were identified; a causal association with Adv‐SM treatment could neither be excluded nor established. In this first real‐life study on patients treated with midostaurin for Adv‐SM, the patients' characteristics, their management, treatment discontinuation, and survival were in line with previous results (compassionate use and clinical trials).